Odpowiedzi

2010-03-22T19:42:31+01:00
-4x+3=11
-4x=11-3
-4x=8
x=-2

5y-3=-18
5y=-15
5y=-3

9-2x=10
-2x=1
x=-1/2

6+2y=-5+3y
2y-3y=-5-6
-y=-11
y=11

pzdr :**
2010-03-22T19:44:08+01:00
-4x+3=11/-3
-4x=8/:(-4)
x=-2

5y-3=-18/+3
5y=-15/:5
y=-3

9-2x=10/-9
-2x=1/:(-2)
x=-1/2

6+2y=-5+3y/-2y
6=-5+y/+5
11=y

b+6=(b+5)+(b-1)
b+6=b+5+b-1
b+6=2b+4/-b
6=b+4/-4
2=b

0,5y-(10-y)=(2y-7)+(8-y)
0,5y-10+y=2y-7+8-y
1,5y-10=y+1/*10
15y-100=10y+10/-10y
5y-100=10/+100
5y=110/:5
y=110/5=22
2010-03-22T19:48:03+01:00
-4x+3=11
-4x=11-3
-4x=8
x=8/-4
x=-2

5y-3=-18
5y=-18+3
5y=-15
y=-15/5
y=-3
9-2x=10
-2x=10-9
-2x=1
x=1/-2
x=-0.5
6+2y=-5+3y
2y-3y=-5-6
-1y=-11
y=-11/-1
y=11

_________________
b+6=(b+5)+(b-1)
b+6=b+5+b-1
b-b-b=5-1-6
-26=-2
b=-2/-2
b=1

0,5y-(10-y)=(2y-7)+(8-y)
0,5y-10-y=2y-7+8-y
0,5y-y-2y+y=-7+8+10
-1,5y=11
y=11/-1,5
y=-7,3